Awareness and Mental Health of Male Drug Addicts With Tuberculosis During the COVID-19 Pandemic - Jia, Dongming; Li, Hai; Xu, Yuming (Frontiers in Psychiatry, 2021)
Introduction: At present, the COVID-19 pandemic remains the most pressing global health issue. Given the significant amount of public awareness, the infection rate and rehabilitation efforts are governed not only by the compliance of transmission mitigation strategies but also by the understanding of coexisting diseases and COVID-19 in patients with chronic infectious diseases. The main goal of this study was to evaluate the differences in demographics, as well as awareness, and risk perception, and emotional reactions, among imprisoned drug addicts with and without tuberculosis (TB) regarding their perceptions and feelings of the COVID-19 pandemic. The secondary goal of the study was also to measure the how the psychological health and nutritional indices of the drug addicts with TB changed during their ongoing rehabilitation. Methods: A total of 265 male drug addicts, 45 of which were positive for TB and the other 220 were negative, were selected as subjects from a mandatory detoxification and rehabilitation center (MDRC).Data were collected through a combination of questionnaires (questions regarding COVID-19 awareness, emotional knowledge and responses, and SCL-90 tests), anthropometric examination, and laboratory blood tests, with which inferential and descriptive statistical analyses were performed. Results: The differences in the accuracy of the responses from the questions probing the awareness of COVID-19 symptoms, transmission, susceptible populations, what kind of mask should be worn, and preventive measures between TB addicts to non-TB addicts were 11.11% vs 60.45%, 57.78% vs 77.27%, 66.67% vs 78.64%, 97.98% vs 97.73%, and 93.33% vs 65.91%, respectively. In the risk perception and emotional reaction sections of the questionnaire, there was significant difference between the two cohorts. In the section assessing the ten dimensions of the SCL-90 scale, there were significant differences between the TB addicts and the Chinese norm. Conclusion: The COVID-19 pandemic we are facing is both an epidemiologic and a psychological crisis. However, while the COVID-19 epidemic will eventually disappear (or become manageable), but the TB epidemic may still persist. To avoid the deleterious consequences of multiple simultaneous epidemics, complementary response measures to COVID-19 and TB can help curb the exacerbation of both situations and, therefore, save lives.